SINTESIS DAN KARAKTERISASI NANOPARTIKEL CaO SEBAGAI BAHAN PENGIKAT LOGAM BERAT - Tika Indriani; Jon Efendi (Jurnal Periodic Jurusan Kimia UNP, 2020)
The increase in industrialization is in line with the increase in pollution of heavy metals that pollute the environment. Such waste needs to be managed properly for laws that are harmful to human health and the environment. Calcium oxide (CaO) is an exceptionally important industrial compound, which is used as toxic-waste remediation agent. Thermal decomposition method has some advantages such as simple process, low cost, ease of obtaining high purity product, etc. Characterization with the FTIR instrument showed the strong band at 3643 cm_1 corresponds to the O-H bonds from the remaining hydroxide.  Bands at 1417 cm-1 and 866 cm-1 correspond to the C-O bond. The wide and strong bands at around 427 cm-1 and 553 cm-1 correspond to the Ca-O bonds. Characterization with the FTIR instrument showed the peaks were higher in intensity and narrower in spectral width, indicating that the products were of good crystallinity.